Systematic review on somatization in a transcultural context among teenagers and young adults: Focus on the nosography blur - Salmon, Mathilde; Sibeoni, Jordan; Harf, Aurélie; Moro, Marie Rose; Ludot-Grégoire, Maude (Frontiers in Psychiatry, 2022)
Aims : Somatic complaints are a frequent cause for consultation in primary care. In a transcultural context, somatic complaints are typically associated with psychological distress. A recent review about somatic symptom disorders in adolescence showed some nosographic heterogeneity and outlined various etiological hypotheses (traumatic, environmental, or neurologic), separate from the cross-cultural considerations. Migrants' children encounter specific problems involving cultural mixing - issues of filiation (familial transmission) and affiliation (belonging to a group). This paper aims to provide a systematic review of somatization in transcultural contexts among teenagers and young adults, aged 13 to 24, over the past decade. Methods: This review adheres to the quality criteria set forth by the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Two authors queried three English databases (Medline, Psycinfo, WebOfScience) about somatization in transcultural contexts (migrant or non-Western population) among teenagers (13-18), young adults (19-24), or both. The methodological process comprised articles selection, data extraction, and then the analysis of emerging themes. Setting selection criteria to limit the transcultural field was difficult. Results: The study analyzed 68 articles. We present a descriptive analysis of the results, centered on three main themes. First, the literature highlights a nosographic muddle reflected in the combination of anxious and depressive symptoms together with the highly variable symptomatology. Second, discrimination issues were prevalent among the migrant population. Lastly, the literature review points out possibilities for improving a care pathway and reducing the diagnostic delay induced by migrants' hesitancy about Western care and the recurrent use of inappropriate diagnostic criteria. Conclusion: This review discusses the links between the nosographic muddle described here and the diagnostic delays these patients experience and raises concerns about rigid diagnostic compartmentalization. The work of the psychiatrist Frantz Fanon is here useful to understand externalized symptoms resulting from physical and psychological confinement. Discrimination issues raise questions about the cultural counter-transference health professionals experience in dealing with young migrants. Defining healthcare professionals representations about somatic complaints in a transcultural context might be a fruitful path to explore in future research. Protocol PROSPERO registration number: CRD42021294132.